(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
An experiment and a statistic study was performed considering the effect of two important input parameters (stretching force and stretching speed) on the stretching behaviour of 6061-0 aluminum sheet in terms of thickness reduction ratio in two types of stretch forming process (post stretching and pre stretching). Experimental tests were carried out using a die with V-shape to stretch the sheet at two selected levels of stretching force and stretching speed and according to the design matrices established by the Design of Experiment (DOE) software (Version 10). Two models with two variable parameters, i.e. stretching force and speed were built by using the response surface methodology (RSM) technique for the two cases of stretching (post and pre stretching), then checked statistically for adequacy purpose by analysis of variance (ANOVA) analysis, and appeared good with 95 % confidence level. It was found that using the post stretch forming process generally gives a lower thickness reduction ratio than that for pre stretching process. This explains the advantages of using post-stretching process to stretch the 6061-0 aluminum sheet alloy.